Principles of geotechnical engineering - Das, Braja M. (PWS, 1998)
This book is about: Soils and rocks; Weight-volume relationships, plasticity, and structure of soil; Classification of soil; Soil compaction; Flow of water in sol; Effective stress concepts; Stresses in a soil mass; ...